HLA-DR in cytotoxic T lymphocytes predicts breast cancer patients' response to neoadjuvant chemotherapy - Saraiva, Diana P. (2018)
This work was supported by iNOVA4Health - UID/Multi/04462/2013 - LISBOA-01-0145-FEDER-007344, Fundacao para a Ciencia e Tecnologia - PD/BD/114023/2015 and PTDC/BBB-BMD/4497/2014. Liga Portuguesa Contra o Cancro.